Experimental study on the impact sound insulation of cross laminated timber and timber-concrete composite floors. (April 2020) - Zhang, Xiaoyu; Hu, Xiamin; Gong, Hongwei; Zhang, Jing; Lv, Zhicheng; Hong, Wan
Highlights: The acoustic behavior of CLT and TCC floors were compared and analyzed. The effective sound insulation improvement schemes were proposed. The impact sound insulation characteristics of different solutions were investigated. Abstract: With the increasing demands for indoor comfort, the sound insulation issues of buildings should not be ignored. The impact sound of floors is the main source of noise between rooms. In this study, impact sound insulation tests were performed on one cross laminated timber (CLT) floor and one timber-concrete composite (TCC) floor to investigate the impact sound insulation performance. Since the sound insulation performance of bare floors is poor, effective sound insulation improvement schemes were proposed, including three kinds of solutions of floating floor and two kinds of solutions of suspended ceiling for TCC floor and CLT floor. In addition, an additional optimization solution of floating floor was also presented for CLT floor. The impact sound insulation performance of two floors with different solutions in full frequency range was compared and analyzed. The test results showed that adding floating floor and suspended ceiling can improve the impact sound insulation performance of floors to a certain degree, and the latter is more effective. The experimental and analytical results could provide a reference for improving the sound insulation of residential floors.